Effect of FABP4 Gene Polymorphisms on Fatty Acid Composition, Chemical Composition, and Carcass Traits in Sonid Sheep - Jiada Xiang; Haofan Li; Zhaoxin Guo; Terigele Li; Takahisa Yamada; Xihe Li; Siqin Bao; Lai Da; Gerelt Borjigin; Ming Cang; Bin Tong (Animals)
Fatty acids (FAs) are a group of organic compounds that are regulated by polygenic and environmental factors and affect the taste, nutritional value, and quality of meat. Lamb meat is rich in FAs required by the human body, which has directed more attention to sheep research and meat production. The fatty acid-binding protein 4 (FABP4) gene is considered a candidate gene that can affect FA composition in livestock. Therefore, the aim of this study was to screen for genetic polymorphisms of FABP4 and confirm the association between these polymorphisms and FAs, chemical composition, and carcass traits in Sonid lambs. The results of the association study showed that g.57764667T>C, g.57764436T>G, g.57764242G>A, and g.57757988A>G were associated with the composition of certain long-chain FAs, and g.57764242G>A, g.57764436T>G, and g.57758026G>A were associated with free amino acid levels. In addition, g.57764667T>C and g.57757988A>G were associated with carcass weight and live weight in Sonid lambs. Therefore, the polymorphisms of the FABP4 gene are expected to be a genetic selection marker for superior traits in Sonid sheep breeding, which also provides new insights into how the ovine FABP4 gene affects traits of lamb quality.